Conceptual review of global outsourcing-offshoring in the last 20 years: Notes on systematic literature review - Gunawan, Arie Indra; Dewi, Andrieta Shintia; Azis, Elvira (Asian Management and Business Review, 2024)
This paper aims to contribute to a better understanding of the relatively comprehensive breadth of information on outsourcing-offshoring from existing and open-source research articles. A systematic literature review was carried out on 700 articles related to global outsourcing to obtain results of scientific studies. The PRISMA method is used to get relevant articles that meet the quality control aspects of the article data used. Research on global outsourcing and offshoring showed significant progress from the start until its peak in 2008. In 2000 global outsourcing was in the implementation stage, requiring a lot of basic and conceptual research to develop global outsourcing activities. After 2008 the topic of global outsourcing research studies decreased. This was because research on global outsourcing became more specific. The 32 topic items grouped into 4 clusters are state-of-the-art research on global outsourcing-offshoring topics in the last 20 years.